Influence Management Lubuk Larangan To Community Empowerment in the District Mandailing Natal - Putra, Erwin; Badaruddin, Badaruddin; Rujiman, Rujiman; Saleh, Arifin Saleh (International Conference on Sciences Development and Technology, 2022)
Lubuk larangan is an effort or activity to raise fish in a Lubuk river section whose location is determined by the community not to be taken by fish within a certain period. Lubuk The larangan has social aspects, economic aspects, environmental aspects, and tourism aspects and is the local wisdom of the people in Mandailing Natal Regency. Lubuk larangan is a hereditary activity that began in the fifties, therefore Lubuk larangan can be said to be wisdom because it has local knowledge, local intelligence, local skills, local resources, local norms and ethics, social processes, social institutions and local beauty whose management leads to community welfare. To improve local wisdom through the management of Lubuk larangan, a regional development model is needed and community empowerment has a link where development aims for the welfare of the community by organizing all aspects of life such as economic, political, social, and cultural as well as customs. The development of Lubuk The larangan in Mandailing Natal Regency still has several problems such as inconsistent management and maintenance. This can be seen from: First, the low yield of freshwater fish in Mandailing Natal Regency where in 2016 it was 1697.80 tons, in 2017 it was 1697.79 tons, and in 2018 it was 1701.46 tons. Second] the lack of professional management to manage the existence of Lubuk larangan in Mandailing Natal Regency. Third, the diversion of the function of Lubuk larangan, especially in the Batang Natal River, the condition of the river is now quite alarming, anywhere in the Batang Natal River and its surroundings there is a Gold Mine. The purpose of this research was to find novelty, analyze, and provide empirical evidence that the Lubuk larangan on management models has a significant effect on regional development through community empowerment in Mandailing Natal Regency. The research method used in this research is quantitative research which is a causal relationship (causal effect). Respondents in this study amounted to 389 people. The measuring instrument used is a questionnaire with the help of the SPSS AMOS 26 program in managing primary data. The results showed that the Lubuk management model larangan had a significant and positive effect on regional development with an estimated value of 0.667 and a P-value of 0.000 < 0.05. Furthermore, there is a significant influence of the management of Lubuk larangan on community empowerment with an estimated value of 0.987 and P-value 0.001 < 0.05. Next, the research findings show that there is a significant effect of community empowerment on regional development with an estimate of 0.396 and p-value 0.025 < α = 0.05. The final test shows that there is a significant influence of the Lubuk larangan management model on regional development through community empowerment in Mandailing Natal Regency. Thus, overall the total effect of the Lubuk Larangan management variable on regional development is 0.391 + 0.396 = 0.787 or 78.7% of the influence of management. Lubuk larangan on regional development indirectly through the community empowerment variable compared to directly which was 0.667 or 66.7%